Use of low birth weight as selecting criterion for the routine surveillance of congenital anomalies of infectious origin. (Colombia Medica, 2008)
Introduction: Surveillance of congenital anomalies receives importance in the world-wide context of eradicating the congenital rubella syndrome. Objective: To identify the congenital anomalies and to consider the low birth weight  a criterion to test IgM for the complex TORCH. Methodology: Surveillance of the congenital specific and non specific anomalies of the congenital rubella syndrome(CRS) and low birth weight in ten hospitals. It was considered as case, everything new born with some congenital anomaly or low weight for the gestational age. Serum tests for rubella, toxoplasmosis, citomegalovirus, herpes and parvovirus were practiced. For the negative cases cariotype was performed. Results: A total of 840 cases were selected, 669 by low weight for the gestational age, 52 by anomalies not related to CRS, 52; by anomalies that could be related to the CRS, 105. The most frequent anomalies were congenital heart diseases,  5.1%; hepatosplenomegalies, 3.9%; and microcephalies, 1.2%. There were confirmatory IgM titles for rubella in 0.5% of cases; toxoplasmosis 1.4%; citomegalovirus 1.5%; parvovirus 1.2%; herpes 0.5%; and positive test for congenital syphilis, 3.7%. In total there were 8.8% positive results for any congenital infectious disease. The relative risk for low birth weight having IgM positive rubella was RR = 2.83 (IC: 1.26:6.36-0.95). Discussion and conclusions: The surveillance for CRS, through the monitoring of febrile in the first year and by the presence of some specific congenital anomalies, could be improved in sensitivity by means of the routine monitoring of congenital anomalies, with the inclusion of low birth weight, like a selecting criterion to study the infectious agents.